Assessment of Fisheries Diversity in Mathabhanga River in the Southwestern Part of Bangladesh (Research in Agriculture Livestock and Fisheries, 2024)
Mathabhanga is an important and well-known river in the southwestern part of Bangladesh due to its role in fish production and as a vital income source for numerous fishermen. The study was carried out from August 2022 to July 2023 to reveal the existing aquatic resources and their composition, along with diversity, richness, and evenness indices. A comprehensive list of 57 distinct fish species has been documented, spanning across 8 orders, 22 families, and 42 genera. Within these, the Cypriniformes order exhibited the highest diversity in terms of both species count and observed individuals. Among the fish species inhabiting the Mathabhanga river, approximately 29.83% are considered threatened in Bangladesh, comprising 14.04% categorized as vulnerable (VU), 14.04% as endangered (EN), and 1.75% as critically endangered (CR). Overall values of the diversity index ranged from 2.45 to 3.15, richness was 3.81 to 6.17, and evenness index was 0.72 to 0.84. The investigation revealed that fish biodiversity in the Mathabhanga River has been steadily decreasing. This study suggested that fisheries should be managed through community-based fisheries management, establishing fish sanctuary, water pollution control, maintenance of fishing gear, and the implementation of the Fish Act for the sustainable management of fish biodiversity in the Mathabhanga River.Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 93-103